Power system security: appreciating the presence of artificial intelligence / Ismail Musirin - Musirin, Ismail (UiTM Press, 2024)
In an era marked by technological advancements and increasing dependence on electricity, ensuring the security of power systems has never been more critical. This book explores the profound impact of artificial intelligence (Al) on maintaining and enhancing the security of power systems. It is designed to provide readers with a thorough understanding of how Al can be harnessed to address the multifaceted challenges of modern power grids. Power System and Understanding the Artificial Intelligence serves as the cornerstone of this book. It introduces readers to the fundamental concepts of power systems and the pivotal role Al plays in their operation. The chapter also examines real-world blackout events in Malaysia,